2007
DOI: 10.1590/s1413-70542007000400026
|View full text |Cite
|
Sign up to set email alerts
|

Linhagens de feijão (phaseolus vulgaris L.): composição química e digestibilidade protéica

Abstract: RESUMOO feijão representa a principal fonte de proteínas para as populações de baixa renda, todavia a digestibilidade dessas proteínas é relativamente baixa. Por isto, os programas de melhoramento genético vêm trabalhando em busca de novas linhagens com níveis protéicos mais elevados. Assim, com a finalidade de fornecer informações aos melhoristas, neste trabalho foram analisadas 21 linhagens de feijão (Phaseolus vulgaris L.), quanto à composição centesimal e mineral, digestibilidade protéica, compostos fenóli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
50
3
38

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(108 citation statements)
references
References 9 publications
13
50
3
38
Order By: Relevance
“…No Brasil, valores entre 0,30 e 2,80g de Ca kg -1 de matéria seca (MS) foram observados em 21 linhagens de feijão (MESQUITA et al, 2007). Variabilidade genética de 0,24 a 0,72g de Ca kg -1 de MS foi verificada em Burundi (BARAMPAMA & SIMARD, 1993) e de 1,7 a 4,0g de Ca kg -1 de MS no México (GUZMÁN-MALDONADO et al, 2000).…”
Section: Genetic Effects Of the Calcium Content In Common Beanunclassified
“…No Brasil, valores entre 0,30 e 2,80g de Ca kg -1 de matéria seca (MS) foram observados em 21 linhagens de feijão (MESQUITA et al, 2007). Variabilidade genética de 0,24 a 0,72g de Ca kg -1 de MS foi verificada em Burundi (BARAMPAMA & SIMARD, 1993) e de 1,7 a 4,0g de Ca kg -1 de MS no México (GUZMÁN-MALDONADO et al, 2000).…”
Section: Genetic Effects Of the Calcium Content In Common Beanunclassified
“…Common bean (Phaseolus vulgaris L), or edible beans or dry beans, present in the Brazilian diet, is an excellent food from a nutritional standpoint since it provides essential nutrients, such as proteins, iron, calcium, vitamins (especially B complex), carbohydrates, fiber and lysine, which is an essential amino acid (Mesquita et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the beans should have desirable cooking features, such as reduced cooking time, good palatability, soft texture of the seed coat and the ability to produce a clear, dense broth after cooking (Mesquita et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, for some time already, emphasis has been given to breeding for increasing the mineral content in bean grains, what is known as biofortification (Beebe, 2010). In these studies, it has been observed that there is genetic variability for the traits that confer nutritional quality to beans, making it possible to select lines with high nutritional value (Beebe et al, 2000;Mesquita et al, 2007;Ribeiro et al, 2008).…”
Section: Introductionmentioning
confidence: 99%